2019
DOI: 10.1111/oik.05877
|View full text |Cite
|
Sign up to set email alerts
|

Diversity patterns from sequentially restored grasslands support the ‘environmental heterogeneity hypothesis’

Abstract: The ‘environmental heterogeneity hypothesis’ (EHH) has been proposed as a mechanism that enables species coexistence through resource partitioning. In accordance with this hypothesis, plant diversity is predicted to increase with variability in resources, but there has been weak support for this hypothesis from experimental studies. The objectives of this research were to 1) characterize how resource availability and heterogeneity (coefficient of variation) change as plant communities develop using sequentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Each plot in each sequence was treated as an independent experimental unit (field replicate) within each sequence (n = 4 per sequence), which was geo-statistically supported by Scott and Baer (2019). To compare trajectories of community development over time among sequences, the effects of AGE (years since seeding) and SEQ (corresponding with planting year) and their interaction on species composition were analyzed using repeated measures permutational multivariate analysis of variance (PERMANOVA) with 1000 permutations using the "adonis" function in the vegan package of R (vegan: Oksanen et al, 2020).…”
Section: Short-term Community Response To Establishment Yearmentioning
confidence: 99%
“…Each plot in each sequence was treated as an independent experimental unit (field replicate) within each sequence (n = 4 per sequence), which was geo-statistically supported by Scott and Baer (2019). To compare trajectories of community development over time among sequences, the effects of AGE (years since seeding) and SEQ (corresponding with planting year) and their interaction on species composition were analyzed using repeated measures permutational multivariate analysis of variance (PERMANOVA) with 1000 permutations using the "adonis" function in the vegan package of R (vegan: Oksanen et al, 2020).…”
Section: Short-term Community Response To Establishment Yearmentioning
confidence: 99%
“…Notably, M. vimineum invasion across the mycorrhizal gradient was associated with homogenization of the ECM-dominance gradient, altering slow cycling organic soil conditions more than inorganic nutrient economies. To the extent that loss of heterogeneity in nutrient economies may promote a reduction in species richness (Scott and Baer 2019), which has known effects on ecosystem functioning (Hooper et al 2005), the longer-term consequences of invasion may be greater than demonstrated here.…”
Section: Discussionmentioning
confidence: 71%
“…Their density and community composition have been shown to vary with forest type (i.e., deciduous vs. coniferous) rather than with the number of tree species (Erdmann et al., 2012 ; Lu, 2021 ; Lu, Bluhm, et al., 2022 ). Mixed forests are likely to provide greater resource and microhabitat diversity, allowing species to occupy different positions in niche space (Chesson, 2000 ; Nielsen et al., 2010 ; Scott & Baer, 2019 ).…”
Section: Introductionmentioning
confidence: 99%